Even one is too much: The economic consequences of being a smoker - Julie L. Hotchkiss; M. Melinda Pitts (Federal Reserve Bank of Atlanta, 2013)
It is well known that smoking leads to lower wages. However, the mechanism of this negative relationship is not well understood. This analysis includes a decomposition of the wage gap between smokers and nonsmokers, with a variety of definitions of smoking status designed to reflect differences in smoking intensity. This paper finds that nearly two-thirds of the 24 percent selectivity-corrected smoking/nonsmoking wage differential derives from differences in characteristics between smokers and nonsmokers. These results suggest that it is not differences in productivity that drive the smoking wage gap. Rather, it is differences in the endowments smokers bring to the market along with unmeasured factors, such as baseline employer tolerance. In addition, we also determine that even one cigarette per day is enough to trigger the smoking wage gap and that this gap does not vary by smoking intensity.
Keywords: J31; I19; C31; 330; smoking wage penalty; wage decomposition; wage differentials